Association between K469E allele of intercellular adhesion molecule 1 gene and inflammatory bowel disease in a Japanese population. Issue 1 (1st January 2003) - Matsuzawa, J; Sugimura, K; Matsuda, Y; Takazoe, M; Ishizuka, K; Mochizuki, T; Seki, S S; Yoneyama, O; Bannnai, H; Suzuki, K; Honma, T; Asakura, H
Abstract : Background and aims: The genetic contribution to inflammatory bowel disease (IBD) is under investigation. Recent evidence indicates a significant linkage between a locus on chromosome 19p13 and IBD. We investigated the association between an intercellular adhesion molecule 1 gene ( ICAM-1 ) polymorphism located on chromosome 19p13 and IBD in a Japanese population. Methods: We compared 207 Japanese patients who had IBD (79 with Crohn's disease (CD); 128 with ulcerative colitis (UC)) with 103 unrelated Japanese controls. We determined R241G and K469E polymorphisms of the ICAM-1 gene using polymerase chain reaction (PCR) techniques. Results: Both frequency and carriage rate of the K469 allele were significantly higher in IBD patients than in controls (allelic frequency, pc =0.0026; carriage rate, pc =0.0034; odds ratio 2.59; 95% confidence interval 1.42–4.68). Furthermore, the frequency of the K469 allele was significantly increased in both CD and UC. Subgroup analysis demonstrated that both K469 allelic frequency and K469 carriage rate were significantly higher in patients with the small bowel and colon type of CD and entire colitis compared with healthy controls. Conclusions: We identified an overall association between IBD and ICAM-1 K469 in a Japanese population. Further studies of this chromosome region are required to elucidate the gene responsible for IBD.